Persepsi Siswa Terhadap Modul Ajar Matematika Pada Kurikulum Merdeka - Aisyah, Sovya Nisdawati; Kurniawati, Yeva (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
Student perception is the way students see in summarizing the various information obtained while interpreting it so that it forms a mindset towards various phenomena that occur. Student perceptions are divided into four dimensions, namely internal, external, knowledge, and benefit dimensions. This study aims to determine student perceptions of mathematics teaching modules implemented in the Merdeka Curriculum. The research method used is descriptive research using a quantitative approach. This study involved seventh grade students. Data were collected through student response questionnaires and documentation. The results of this study are that the internal dimension is in the good category with a result of 71.2%. In the external dimension, the result is 71.4% which is included in the good category. In the knowledge dimension, the result is 71.3% which is included in the good category. In the benefit dimension, the result is 70.9% which is included in the good category. The results show that from the four dimensions of perception show that students have a good perception of the use of the independent curriculum teaching module used in daily mathematics learn.